Diagnosis exjuvantibus of a persistent pleural effusion - José M. Porcel (Journal of Community Hospital Internal Medicine Perspectives, 2013)
The diagnosis of uremia-associated effusion is one of exclusion. A patient with an unexplained chronic pleural exudate, which cleared with dialysis, is reported. The differential diagnosis of pleural effusions in patients with chronic kidney disease and the management of uremic pleuritis is briefly discussed.